The Development of a Taxonomy of Wrongdoing in Medical Practice and Research - DuBois, James M. (2012)
“Ethical disasters” or egregious violations of professional ethics in medicine often receive substantial amounts of publicity, leading to mistrust of the medical system. Efforts to understand wrongdoing in medical practice and research are hampered by the absence of a clear taxonomy. This article describes the authors’ process of developing a taxonomy based on: (1) reviews of academic literature, ethics codes, government regulations, and cases of wrongdoing; (2) consultation with experts in health law and healthcare ethics; and (3) application of the taxonomy to published cases of wrongdoing in medical research and practice. The resulting taxonomy includes 14 categories of wrongdoing in medical practice, and 15 categories of wrongdoing in medical research. This taxonomy may be useful to oversight bodies, researchers who seek to understand and reduce the prevalence of wrongdoing in medicine, and librarians who index literature on wrongdoing.